THE ROLE OF ENVIRONMENT IN MENTAL TOUGHNESS IN WUSHU: A REVIEW OF THE LITERATURE - 1. Uma Shankar , 2. DR. Surjeet Singh Kaswan (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Mental toughness is a crucial aspect of success in Wushu, a traditional Chinese martial art that requires physical and mental discipline. The environment in which Wushu athletes train and compete plays a significant role in shaping their mental toughness. This review aims to explore the relationship between environment and mental toughness in Wushu, examining the impact of factors such as training facilities, coaching, and social support on athletes' mental resilience and performance. A comprehensive review of the literature reveals that the environment can have a profound impact on mental toughness in Wushu, and that athletes, coaches, and organizations can take steps to create supportive and challenging environments that foster mental toughness and promote success in the sport.